Characterization of cross-linked porous gelatin carriers and their interaction with corneal endothelium: biopolymer concentration effect. - Jui-Yang Lai (PLoS ONE, 2013)
Cell sheet-mediated tissue regeneration is a promising approach for corneal reconstruction. However, the fragility of bioengineered corneal endothelial cell (CEC) monolayers allows us to take advantage of cross-linked porous gelatin hydrogels as cell sheet carriers for intraocular delivery. The aim of this study was to further investigate the effects of biopolymer concentrations (5-15 wt%) on the characteristic and safety of hydrogel discs fabricated by a simple stirring process combined with freeze-drying method. Results of scanning electron microscopy, porosity measurements, and ninhydrin assays showed that, with increasing solid content, the pore size, porosity, and cross-linking index of carbodiimide treated samples significantly decreased from 508±30 to 292±42 µm, 59.8±1.1 to 33.2±1.9%, and 56.2±1.6 to 34.3±1.8%, respectively. The variation in biopolymer concentrations and degrees of cross-linking greatly affects the Young's modulus and swelling ratio of the gelatin carriers. Differential scanning calorimetry measurements and glucose permeation studies indicated that for the samples with a highest solid content, the highest pore wall thickness and the lowest fraction of mobile water may inhibit solute transport. When the biopolymer concentration is in the range of 5-10 wt%, the hydrogels have high freezable water content (0.89-0.93) and concentration of permeated glucose (591.3-615.5 µg/ml). These features are beneficial to the in vitro cultivation of CECs without limiting proliferation and changing expression of ion channel and pump genes such as ATP1A1, VDAC2, and AQP1. In vivo studies by analyzing the rabbit CEC morphology and count also demonstrate that the implanted gelatin discs with the highest solid content may cause unfavorable tissue-material interactions. It is concluded that the characteristics of cross-linked porous gelatin hydrogel carriers and their triggered biological responses are in relation to biopolymer concentration effects.